Assessment of perceived stress and daytime somnolence in health science students in North India - Singh, Mohita; Sethi, Jyoti; Hasan, Shadan; Kaushik, Navneet K. (International Journal Of Community Medicine And Public Health, 2025)
Background: Recent studies have increasingly underscored the high prevalence of stress and sleep disturbances among medical students that adversely impacts their general well-being and academic performance. The present research was conducted with the aim to assess the perceived stress and daytime sleepiness levels in medical and paramedical students. Additionally, relationship between the two was also examined. Methods: This cross-sectional study was conducted in 200 undergraduate students in the age group of 18-25 years, pursuing medical and paramedical courses at a government medical college in Karnal district, Haryana, north India. Perceived stress scale (PSS)-10 was used to evaluate the perceived stress level and Epworth sleepiness scale (ESS) to assess daytime somnolence. Association between study variables was determined using Pearson’s correlation analysis. Results: Study sample encompassed 51% (n=102) females, 49% (n=98) males and had mean age of 20.46 (SD=1.47) years. 84% (n=168) of students reported moderate stress while 12% (n=24) demonstrated high stress levels. Around four out of five (n=159) experienced excessive level of daytime sleepiness. Pearson’s correlation analysis demonstrated a significant, positive (r=0.15, p=0.03) association between perceived stress and daytime somnolence. Conclusions: Our findings were concerning as the prevalence of moderate to severe stress and excessive daytime sleepiness was found to be alarmingly high, regardless of gender. Also, daytime sleepiness showed positive relationship with perceived stress. There is an urgent need to identify and address these issues well in time.